The Gut Microbiome as a Major Regulator of the Gut-Skin Axis - Salem, Iman; Ramser, Amy; Isham, Nancy; Ghannoum, Mahmoud A. (Frontiers in Microbiology, 2018)
The adult intestine hosts a myriad of diverse bacterial species that reside mostly in the lower gut maintaining a symbiosis with the human habitat. In the current review, we describe the neoteric advancement in our comprehension of how the gut microbiota communicates with the skin as one of the main regulators in the gut-skin axis. We attempted to explore how this potential link affects skin differentiation and keratinization, its influence on modulating the cutaneous immune response in various diseases, and finally how to take advantage of this communication in the control of different skin conditions.